Analisis Komprehensif Profil Karakteristik Anak Usia Dini Dengan Risiko Hambatan Kognitif: Studi Kasus Tunggal di TPA Harapan Keluarga - Nindya Seva Kusmaningsih; Khoirun Annisah; Abdul Aziz (Jurnal Impresi Indonesia, 2025)
This case study aims to analyze the initial screening findings of a preschool child suspected of having special needs, forming the basis for targeted intervention recommendations. Using a qualitative approach with a single-case study design, the main analysis unit was Subject S-1 (male, 2 years and 5 months), with primary data derived from screening documents. Data were analyzed descriptively through reduction, comparative data presentation, and verification against child development norms for ages 2–3 years and Global Developmental Delay (GDD) criteria. The screening results indicated a strong cognitive impairment associated with GDD (IDAI, 2023). The deviations were identified across multiple domains: (1) Cognitive/Receptive (difficulty understanding simple instructions), (2) Fine Motor (inconsistent/stiff muscle tone and inability to pinch), (3) Expressive Language (limited verbal communication), and (4) Social-Emotional (isolated behavior and lack of affective response during physical interactions). Oral sensory difficulties (difficulty chewing) further reinforced the multidimensional nature of the delay. These findings confirm significant developmental red flags. Immediate recommendations include referral for clinical assessment/diagnosis by professionals (psychologists or pediatric specialists). This diagnosis is critical for determining the etiology and formulating a multidisciplinary intervention program (speech therapy and occupational therapy) to take advantage of the subject’s brain plasticity during early childhood (WHO/UNICEF, 2020) and optimize developmental potential.